The acquisition of personal pronouns’ comprehension and production in French-speaking children: Toward the ability to embody characters’ perspectives in various pictured speech interactions - Jean Xavier; Clément Villières; Camille Bélichard; Chloé Chêne; Nicolas Bodeau; Sébastien Fixary; Lucie Broc; Michel Fayol (PLoS ONE, 2025)
Language acquisition involves the ability to switch perspectives according to the partners’ roles in the speech context. This ability, involving morphosyntactic and pragmatic aspects, is fundamental in the acquisition process of personal pronouns (PersP). Our aim is to analyze, in spoken French, the acquisition of comprehension and production of PersP according to different perspectives (1p, 2p, 3p) and functions [subject (S); direct object (DO) and indirect object (IO) clitics]. 110 children aged from 6 to 13 participated. Comprehension and production of PersP were evaluated through an experimental protocol consisting of various ecological situations of the children’s daily life, in a comic strip format. Sentences had two levels of difficulty: D1, involving S and DO; and D2 involving S, DO and IO PersP. We found an age effect on the scores for the two tasks. Scores for expected answers were higher in the comprehension (1) than in the production task (2). We identified a significant increase in the mean scores, after an estimated breakpoint of 8 years for (1), and after the two estimated breakpoints of 8 and 10 years for (2). In (2) we found significantly better performances for D1 than for D2 sentences. In D1, unexpected answers occur more significantly on the DO than on the S, and in D2 they occur first on the DO, then on the IO and finally on the S. In D1 sentences, the DO is pronominalized but challenging for gender; in D2 sentences it is mainly omitted, like for IO. After the age of 6, children’s performances in the acquisition of PersP’s comprehension and production increase with age. At the age of 8 for the comprehension task, and at the ages of 8 and 10 for the production task we identified a significant increase in the children’s performances. In this last task, the difficulties could be explained by its computational complexity in terms of morphosyntactic and pragmatic constraints The difficulties were focused on the use of object pronouns and mainly DO. We suggest that, in D2 sentences, children focus primarily on the partners of the interaction involved in the speech context (designated by S and IO), rather than on the object of the interaction (DO).